Pelayanan Hamba Tuhan dalam Tugas Penggembalaan Jemaat - Joko Santoso (SANCTUM DOMINE: JURNAL TEOLOGI, 2019)
The Servant of God in the pastoral care of the congregation in the millennial era was subjected to severe testing and challenges. The influence of the progress and development of civilization greatly impacts and erodes the truth values that have been instilled by church fathers. Purity as a servant of God in carrying out the ministry of pastoral care is at stake. Loyalty to the Bible as a source of behavior and the carrying out of church service calls is questionable. And service as a servant of God has been a struggle in life throughout church history. This study aims to find the extent to which there has been a shift in the value of God's servants in carrying out their ministry. The result is a clear illustration of how important it is as a servant of God to remain consistent in keeping with the Bible, the source of behavior and measuring tools for the life of God's servants as a form of accountability for carrying out the ministry of pastoral care to God.